Exploring obstacles to critical care trials in the UK: A qualitative investigation. (February 2017) - Pattison, Natalie; Arulkumaran, Nishkantha; Humphreys, Sally; Walsh, Tim
Background: Clinical trials in critical care are often resource-intense, with many unique challenges. Barriers to effective recruitment and implementation of study intervention have not been explored in a UK context. Aim: To identify facilitating factors and barriers to enrolling patients into critical care clinical trials within the UK from clinician's perspectives. Methods: A qualitative interview study was undertaken on behalf of the National Institute of Health Research critical care specialty group, in which research active clinicians across different Clinical Research Networks were interviewed. A loosely structured interview schedule was used, based on themes generated from the literature associated with accessing critical care trials. Research teams (critical care doctors, research nurses, and trial coordinators) from hospitals from each Clinical Research Network were contacted to try to achieve representation across the UK. Results: Interviews were carried out across nine UK Clinical Research Networks with a range of doctors and research nurses. All hospitals were teaching hospitals with varying research nurse numbers and allocated consultant research sessions. There were a range of six to nine ongoing clinical trials in critical care for each centre representative interviewed. Data were analysed using framework analysis, and six final themes were identified related to factors associated with: centre, unit, resources, study, clinician, and patient/family. The most commonly cited barrier to conducting clinical trials was related to resources, namely insufficient human and financial resources, leading to staff and study recruitment difficulties. Clinical uncertainty and equipoise regarding comparative merits of trials were challenging in terms of engaging critical care teams. A number of patient and family factors added complexities in terms of recruitment; however, refusal rates were generally reported as low. Conclusion: Flexibility in funding and employment by research teams enables continuity of studies and staff. Innovative measures to incentivise research nurses and clinical teams can help recruit more patients into trials. Research teams are highly committed to providing cover to recruit critical care trials, and a significant effort to anticipate barriers is undertaken; these endeavours are summarised to provide guidance for other teams wishing to address any potential difficulties.